Criopreservação de semen equino previamente refrigerado com e sem plasma seminal por 12 horas - Resende, Helene Lacerda de [UNESP]; Oliveira, Jhonnatha Paulo; Ecker, Marcely Koroline Conceição; Guasti, Priscilla Nascimento; Papa, Frederico Ozanam [UNESP]; Jacob, Júlio César Ferraz (My University, 2013)
In the equine species, the use of frozen semen has limiting factors as the need for skilled labor, the high cost of equipment, as well as an appropriate place on the farms to the handling of semen. In order to evaluate the effect of seminal plasma on cooling of equine semen for 12 hours before cryopreservation, this study was conducted with five stallions of Mangalarga Marchador breed, aged between 4 and 8 years old. For this experiment, 15 semen collections were performed, each ejaculate was divided into three groups and each group was divided into two subgroups, using different media extenders (Botu-Semen® and Botu-Turbo®). In Group I (control), the semen was frozen immediately after collection; in Group II, the seminal plasma was maintained during the cooling and in Group III, the seminal plasma was removed before cooling. After thawing, the sperm parameters were analyzed using CASA and membrane integrity was evaluated by the fluorescent probes carboxyfluorescein diacetate and propidium iodide. Statistical analysis was performed by ANOVA and Tukey’s test. There was no significant differences (P>0.05) between the semen samples with and without seminal plasma prior to freezing for all sperm parameters evaluated, total motility (50.5 vs 50.6), progressive motility (21.3 vs 24.1) and plasma membrane integrity (26.2 vs 28). The analyzed data showed that the cooling of equine semen for 12 hours before cryopreservation is an effective method that enables a better use of the ejaculate, regardless of maintenance or removal of seminal plasma during the semen storage.

Na espécie equina a utilização do sê- men congelado tem fatores limitantes como a necessidade de mão de obra especializada, o alto custo dos equipamentos, assim como locais apropriados nos haras para manipulação do sêmen. Com o objetivo de avaliar o efeito do plasma seminal na refrigeração do sêmen equino por 12 horas antes da criopreservação, o estudo foi conduzido com cinco garanhões da raça Mangalarga Marchador, com idade entre 4 e 8 anos. Foram realizadas 15 colheitas de sêmen, sendo que cada ejaculado foi divido em três grupos, e cada grupo foi dividido em dois subgrupos, utilizando diferentes meios extensores (Botu-Sêmen® e Botu-Turbo®). A amostra do Grupo I (controle) foi congelada logo após a coleta, o sêmen do Grupo II teve o plasma seminal mantido durante a refrigeração e o sêmen do Grupo III teve o plasma seminal retirado para refrigerar. Após o descongelamento, os parâmetros espermáticos de motilidade foram analisados utilizando CASA e a integridade da membrana plasmática foi avaliada por meio de sondas fluorescentes de diacetato de carboxifluoresceína e iodeto de propídio. A aná- lise estatística foi realizada através da ANOVA e teste de Tukey. Não houve diferença significativa (P>0,05) entre o sêmen, previamente a congelação, refrigerado com e sem plasma seminal para todos os parâmetros espermáticos avaliados, sendo estes motilidade total (50,5 vs 50,6), motilidade progressiva (21,3 vs 24,1) e integridade de membrana plasmática (26,2 vs 28). Os dados analisados indicaram que a refrigeração do sêmen equino por 12 horas antes da criopreservação é um método eficaz, que possibilita um melhor aproveitamento do ejaculado, independentemente da manutenção ou remoção do plasma seminal durante a refrigeração.
Cryopreservation of Equine Semen previously cooled with and without seminal plasma for 12 hours
Keywords: Stallion; Freezing; Fractions of semen; Extender; Garanhão; Congelação de sêmen; Frações do sêmen; Extensor de sêmen